Pendekatan-Pendekatan dalam Ilmu Manajemen dan Implikasinya pada Perkembangan Ilmu Manajemen Pendidikan Islam - Winarti, Endah (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2022)
The development of management science that has spawned various approaches, bringing implications for the development of Islamic Education management science. In a high era of current competition, educational institutions require management theories that can be practiced to create an institution that can endure in the long term. The purpose of article is to discuss approaches that develop in the science of management, including: operational, behavioral, system and quantitative, as well as its implications for the development of Islamic Education management and practices. The results showed that the operational approach, has come to the awareness of quality, which implicates the adoption of the concept of Total Quality Management. The behavior approach, has spawned human consciousness as the main resource, which implicates the development of human resources management concept of Islamic education institutions. The system approach, has given rise to awareness of the environment, which implicates the emergence of the concept of educational institutions as a social system that includes inputs, processes and outputs. And the quantitative approach spawned a management view as a measurable logical entity, thereby implicates the efforts to increase efficiency in Islamic education management areas.